PROMOTING ENGLISH LEARNERS’ PRONUNCIATION OF INFLECTIONAL SUFFIXES-S AND -ES THROUGH JAZZ 13 CHANTS - Lestari, Putri Devi; Laduni, Mochamad Ndaru Purwaning; Bandjarjani, Wahju (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2017)
This paper aims at sharing the writers‘ experiences in tacklingthe English learners‘ problems in pronouncing the inflectional suffixes–sand –es by means of a type of media, called ―Jazz Chants‖. These areCarolyn Graham's snappy, upbeat chants and poems that use jazz rhythmsto illustrate the natural stress and intonation patterns of conversationalAmerican English. Based on the observations during pronunciationpractice classes towards the performances in pronouncing the inflectionalsuffixes -s and -es of the English learners or students in the first semesterof the English Language Education Department of the Faculty of TeacherTraining and Education in Universitas PGRI Adi Buana Surabaya, it turnsout that employing Jazz Chants has made it easier for the learners to beaware of the different ways of pronouncing the inflectional suffixes –sand–es(/s/, /z/, and /ɪz or əz/) in different type of the final sound of a word.In other words, the learners‘ pronunciation of inflectional suffixes –s and–es is promoted through the implementation of Jazz Chants duringpronunciation practices.